2017
DOI: 10.3329/pa.v28i2.33471
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield performance of local T Aman genotypes in southern region of Bangladesh

Abstract: The present experiment was conducted at the Research Field Laboratory of the Department of Agricultural Botany, Patuakhali Science and Technology University (PSTU), Patuakhali during the period from July to December 2013 to evaluate among the local T Aman rice genotypes for obtaining the most productive genotype regarding growth and yield performance under southern region. Four local T Aman rice genotypes namely Lalchicon, Lalmota, Moulata and Mothamota were used as planting materials and laid out in RCBD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It might be due to the fact that the spacing 35cm × 15cm provided enough nutrients, light and air which played vital role in producing more effective tillers hill -1 .The highest number of grains panicle -1 (119.52), grain yield (3.80 t ha -1 , Figure 2), biological yield (9.43 t ha -1 ), harvest index (40.29) was obtained from 25cm × 15cm row spacing and the lowest number of grains panicle -1 (111.65), biological yield (8.57 t ha -1 ), harvest index (34.46) from the row spacing 15 cm × 15 cm and lowest grain yield (3.14 t ha -1 ) was obtained from the row spacing 20cm × 15 cm (Table 2). A group researcher found that number of grains differed significantly due to variety [16,17]. The highest number of grains panicle -1 was mainly responsible for this highest grain yield.…”
Section: Effect Of Row Spacing On Yield Contributing Characters and Ymentioning
confidence: 99%
“…It might be due to the fact that the spacing 35cm × 15cm provided enough nutrients, light and air which played vital role in producing more effective tillers hill -1 .The highest number of grains panicle -1 (119.52), grain yield (3.80 t ha -1 , Figure 2), biological yield (9.43 t ha -1 ), harvest index (40.29) was obtained from 25cm × 15cm row spacing and the lowest number of grains panicle -1 (111.65), biological yield (8.57 t ha -1 ), harvest index (34.46) from the row spacing 15 cm × 15 cm and lowest grain yield (3.14 t ha -1 ) was obtained from the row spacing 20cm × 15 cm (Table 2). A group researcher found that number of grains differed significantly due to variety [16,17]. The highest number of grains panicle -1 was mainly responsible for this highest grain yield.…”
Section: Effect Of Row Spacing On Yield Contributing Characters and Ymentioning
confidence: 99%
“…Dutta (2002) discovered that the yield was influenced by the quantity of filled grains per panicle. A study by Howlader et al (2017) suggests that genetic makeup may have contributed to substantial variation in thousand grain weight. Khush (1997) suggested that thousand grain weight is a crucial yieldattributing genetic traits those are known to be least affected by the environment.…”
Section: Discussionmentioning
confidence: 99%